Determinants of Successful Integration of E-learning into Higher Education - Gupta, Ritu Mittal; ., Anusha (Indian Journal of Extension Education, 2020)
The recent lockdown followed by spread of global pandemic COVID-19 compelled schools and colleges to continue education by online mode. Such scenario calls Universities to blend e-learning with class room learning in future, too. The use of e-learning is influenced by various factors. Therefore, the current study was undertaken to identify various factors which affect students’ perception towards e-learning. Data was collected through questionnaire from 200 students from four well-established universities of Punjab. The results show that out of ten factors of Technology Acceptance Mode considered in the study, subjective norm and computer skills were most prominent in determining integration of e learning into higher education. There is need to enhance the computer skills of students for successful implementation of e-learning in universities. Further, as subjective norm was leading factor so administrations and teachers should encourage students to use web-based learning.